2019
DOI: 10.1126/scitranslmed.aaw3163
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines inducing immunity to Lassa virus glycoprotein and nucleoprotein protect macaques after a single shot

Abstract: Lassa fever is a major threat in Western Africa. The large number of people living at risk for this disease calls for the development of a vaccine against Lassa virus (LASV). We generated live-attenuated LASV vaccines based on measles virus and Mopeia virus platforms and expressing different LASV antigens, with the aim to develop a vaccine able to protect after a single shot. We compared the efficacy of these vaccines against LASV in cynomolgus monkeys. The vaccines were well tolerated and protected the animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
102
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(126 citation statements)
references
References 53 publications
17
102
0
7
Order By: Relevance
“…In vivo protection was not extensively tested in this study in which few cross-reactive GP2 mAbs were raised, and the lack of protection conflicts with a prior report by Ruo et al demonstrating the neutralizing property of GP2 specific mAbs that bind conserved epitopes on GP2 subunit of Old World and New World arenaviruses. Furthermore, recent vaccine studies have also shown that non-NAbs may contribute to protection against clinical disease in guinea pig and NHP models [50,51,62]. However, the GP binding site of the vaccine-induced non-NAbs were not mapped in these studies.…”
Section: Gp Epitope Variation Among Lasv Lineagesmentioning
confidence: 90%
See 3 more Smart Citations
“…In vivo protection was not extensively tested in this study in which few cross-reactive GP2 mAbs were raised, and the lack of protection conflicts with a prior report by Ruo et al demonstrating the neutralizing property of GP2 specific mAbs that bind conserved epitopes on GP2 subunit of Old World and New World arenaviruses. Furthermore, recent vaccine studies have also shown that non-NAbs may contribute to protection against clinical disease in guinea pig and NHP models [50,51,62]. However, the GP binding site of the vaccine-induced non-NAbs were not mapped in these studies.…”
Section: Gp Epitope Variation Among Lasv Lineagesmentioning
confidence: 90%
“…Another approach is to present whole LASV GP complex on vaccine constructs (e.g., viral vectors, virus-like particles (VLP), and replicons), as practiced in most of the successful LASV vaccine candidates [23,46,50,51,69]. This presents both variable and conserved GP subunit epitopes, as well as quaternary GP epitopes, to induce B-cell and T-cell mediated protection.…”
Section: Implications Of Lasv Diversity On Vaccine Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…This vaccine mediates expression of CHIKV virus-like particles. Using a similar approach, a measles-based Lassa virus vaccine has been developed and was shown to protect cynomolgus monkeys from a Lassa virus challenge [11].…”
Section: Introductionmentioning
confidence: 99%